Belajar Bahasa Indonesia di Era Digital: Kajian Literatur Tentang Peran dan Pemanfaatan Media Digital dalam Meningkatkan Pembelajaran Bipa - Manullang, Elkana Pujiando; Manullang, Syahma Fitri; Saragih, Mutiara; Safinatul Hasanah Harahap (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Technological progress cannot be separated from progress in the field of education. one of which is the spread of digital technology in various fields. BIPA (Indonesian Language for Foreign Speakers) is an effective strategy to promote Indonesia on the international stage. To implement BIPA learning effectively, it is important to apply a modern and relevant approach. Digital media is technology that facilitates human activities. The method used in this research is literature study. This method was carried out by collecting nine academic and conference papers published in Indonesian language journals from the Google Scholar database. The literature taken ranges from 2019 to 2024. In the nine articles analyzed, studies on the use of digital media in BIPA learning apply technological media used in BIPA learning at certain levels.